Haematuria in the Elderly: a Review - Dabota Buowari, Yvonne (Journal of Aging Research And Healthcare, 2019)
Haematuria is a common compliant in the elderly. Microscopic haematuria is first suspected after a dipstick in urine and confirmed with urine microscopy. The causes of haematuria in the elderly may be renal or extra-renal including clotting disorders. This article is a review on haematuria in the elderly.
Keywords: Haematuria; Urine; Elderly; Urinary Tract.